Epigenetic predictors of lifestyle traits applied to the blood and brain. Issue 2 (19th April 2021) - Gadd, Danni A; Stevenson, Anna J; Hillary, Robert F; McCartney, Daniel L; Wrobel, Nicola; McCafferty, Sarah; Murphy, Lee; Russ, Tom C; Harris, Sarah E; Redmond, Paul; Taylor, Adele M; Smith, Colin; et al.
Abstract: Modifiable lifestyle factors influence the risk of developing many neurological diseases. These factors have been extensively linked with blood-based genome-wide DNA methylation, but it is unclear if the signatures from blood translate to the target tissue of interest—the brain. To investigate this, we apply blood-derived epigenetic predictors of four lifestyle traits to genome-wide DNA methylation from five post-mortem brain regions and the last blood sample prior to death in 14 individuals in the Lothian Birth Cohort 1936. Using these matched samples, we found that correlations between blood and brain DNA methylation scores for smoking, high-density lipoprotein cholesterol, alcohol and body mass index were highly variable across brain regions. Smoking scores in the dorsolateral prefrontal cortex had the strongest correlations with smoking scores in blood ( r = 0.5, n = 14, P = 0.07) and smoking behaviour ( r = 0.56, n = 9, P = 0.12). This was also the brain region which exhibited the largest correlations for DNA methylation at site cg05575921 – the single strongest correlate of smoking in blood—in relation to blood ( r = 0.61, n = 14, P = 0.02) and smoking behaviour ( r = −0.65, n = 9, P = 0.06). This suggested a particular vulnerability to smoking-related differential methylation in this region. Our work contributes to understanding how lifestyle factors affect the brain and suggest that lifestyle-related DNA methylation is likely to be both brain region dependent and in many cases poorly proxied for by blood. Though these pilot data provide a rarely-available opportunity for the comparison of methylation patterns across multiple brain regions and the blood, due to the limited sample size available our results must be considered as preliminary and should therefore be used as a basis for further investigation. Graphical Abstract: